2023
DOI: 10.1186/s13075-023-03035-5
|View full text |Cite
|
Sign up to set email alerts
|

FTO-mediated m6A demethylation of pri-miR-3591 alleviates osteoarthritis progression

Abstract: Objectives Increasing evidence have demonstrated the N6-methyladenosine (m6A) plays critical roles in osteoarthritis (OA) progression, but the role of m6A in OA has not been completely illuminated. Herein, we investigated the function and underlying mechanism of m6A demethylase fat mass and obesity-associated protein (FTO) in OA progression. Materials and methods The FTO expression was detected in mice OA cartilage tissues and lipopolysaccharide (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A methylated RNA immunoprecipitation sequencing (MeRIP-seq) study unveiled that FTO knockdown affects the steady-state levels of several miRNAs [ 48 ]. Previous research has also demonstrated that FTO can exert effects in various cancers and inflammatory diseases by influencing miRNA maturation [ 49 , 50 ]. In our findings, overexpression of FTO in MH-S cells resulted in the downregulation of mature miR-192 and pre-miR-192 expression, concomitant with an accumulation of pri-miR-192.…”
Section: Discussionmentioning
confidence: 99%
“…A methylated RNA immunoprecipitation sequencing (MeRIP-seq) study unveiled that FTO knockdown affects the steady-state levels of several miRNAs [ 48 ]. Previous research has also demonstrated that FTO can exert effects in various cancers and inflammatory diseases by influencing miRNA maturation [ 49 , 50 ]. In our findings, overexpression of FTO in MH-S cells resulted in the downregulation of mature miR-192 and pre-miR-192 expression, concomitant with an accumulation of pri-miR-192.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that m6A modification, which is mediated by related enzymes, such as METTL3 and FTO, mediates miRNA maturation and expression. [27,28] For instance, FTO enhances m6A demethylation of pri-miR-3591, which impedes miR-3591-5p maturation and inhibits its expression, thereby alleviating osteoarthritis progression. [28] Here, we found m6A modification sites in the pri-miR-199a-5p sequence via the use of the SRAMP website, suggesting that the m6A modification of pri-miR-199a-5p may lead to abnormal miR-199a-5p expression in MI/ RI.…”
Section: Micrornas (Mirnas) Are Important Components Of Noncodingmentioning
confidence: 99%
“…[27,28] For instance, FTO enhances m6A demethylation of pri-miR-3591, which impedes miR-3591-5p maturation and inhibits its expression, thereby alleviating osteoarthritis progression. [28] Here, we found m6A modification sites in the pri-miR-199a-5p sequence via the use of the SRAMP website, suggesting that the m6A modification of pri-miR-199a-5p may lead to abnormal miR-199a-5p expression in MI/ RI. Thus, we explored whether pri-miR-199a-5p is affected by m6A methylation-related enzymes, thereby affecting miR-199a-5p maturation and expression in MI/RI.…”
Section: Micrornas (Mirnas) Are Important Components Of Noncodingmentioning
confidence: 99%
“…Increasing evidences have shown that METTL3, WTAP, FTO and ALKBH5 are aberrantly expressed in OA chondrocytes and involved in OA pathogenesis by regulating chondrocyte proliferation, apoptosis, extracellular matrix (ECM) degradation through related signal pathways [ 69 , 72 , 80 , 84 ]. For example, Lin et al have revealed that WTAP-mediated miR-92b-5p/TIMP4 axis plays crucial role in OA development.…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%
“…In addition, FTO and ALKBH5 are identified as potential targets to alleviate OA. For example, Liu et al reported that overexpression of FTO inhibited the miR-3591-5p maturation via regulating demethylation of pri-miR-3591, and then downregulated PRKAA2 to alleviate cartilage damage in OA [ 80 ]. Cai and colleagues found that upregulating FTO promoted proliferation, inhibited apoptosis and inflammation in LPS-induced C28/I2 cells through the miR-515-5p/ TLR4/MyD88/NF-κB axis [ 81 ].…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%